Exercise training reduces the flesh firmness of juvenile hāpuku ( Polyprion oxygeneios ) with a hypertrophic reduction in muscle fibre density - JR Khan; S Pether; M Bruce; SP Walker; Y Hemar; NA Herbert (New Zealand Journal of Marine and Freshwater Research, 2015)
Consumers base the organoleptic quality of fish on factors such as texture, which can be altered by exercise. The effect of exercise on the fillet firmness of hāpuku ( Polyprion oxygeneios ) was investigated to determine whether exercise would yield a firmer and more desirable product. To achieve this, the firmness and muscle fibre density (MFD) of fillets from fish exercised for 8 weeks at 0.0, 0.75 or 1.5 body lengths/second (BL s −1 ) was assessed. Firmness was significantly lower in the 0.75 BL s −1 and 1.5 BL s −1 exercised fish than the 0.0 BL s −1 group. MFD was also significantly lower in the exercise treatments. This is explained by an increase in the median fibre size with exercise implying that exercise stimulated muscle fibre hypertrophy, leading to lowered MFD. Assuming that firmer flesh is perceived to be more desirable, exercise may have little value in the production of hāpuku.

Developing yellowtail kingfish ( Seriola lalandi ) and hāpuku ( Polyprion oxygeneios ) for New Zealand aquaculture - JE Symonds; SP Walker; S Pether; Y Gublin; D McQueen; A King; GW Irvine; AN Setiawan; JA Forsythe; M Bruce (New Zealand Journal of Marine and Freshwater Research, 2014)
Two high value species, yellowtail kingfish ( Seriola lalandi ) and hāpuku (groper, Polyprion oxygeneios ), have been identified as suitable new candidates for New Zealand aquaculture. This paper reviews the research by NIWA and collaborators conducted to test the biological, technological and economic feasibility of farming these two species. NIWA now has the capability to produce sufficient kingfish fingerlings per year to meet the needs of the early stages of an industry. Advances in hāpuku aquaculture have also been significant, from spawning in captivity through to the selection of juveniles for improved growth. Recently, the first spawning of captive hāpuku F1 broodstock and production of F2 eggs, larvae and juveniles was achieved. Although hāpuku larval survival remains variable, the ability to close the life cycle, and the availability of domesticated broodstock, provide a significant step forward and increase the chances of this species being commercially farmed.